IMPACT OF VITAMIN D DEFICIENCY OR INSUFFICIENCY ON THE SEVERITY OF COVID-19 IN HOSPITALIZED PATIENTS - Olga A. Golubovska; Kyrylo O. Chalyy; Oleksandra V. Bezrodna; Anastasiia A. Holubovska (Клінічна та профілактична медицина)
Introduction. Among the risk factors for severe, complicated course of coronavirus disease 2019 (COVID-19), the potential role of vitamin D deficiency or insufficiency is attracting increasing attention.